The Development and Adjustment of Road and Rail Transportation Network in Poland in 1918-2000 - Kaliński, Janusz (Studia Historiae Oeconomicae, 2006)
The period of 123 years of political non-existence of the state of Poland resulted in deep disintegration of the Polish territories under the rule of three neighboring countries that made every effort to blur the old frontier lines, drawing new ones which severed centuries-long economic relations. The unfavorable political circumstances had their influence on transporta- tion which in the 19th century underwent fast developement and modernization.